Impact of Credit Diversification on Credit Risk of Nepalese Commercial Banks - Dhungel, Bidur (Nepalese Journal of Economics, 2024)
This study examines the impact of credit diversification on the credit risk of Nepalese commercial banks. Non-performing loan and net interest margin are the selected dependent variables. The selected independent variables are loan to deposit ratio, overdraft loan, term loan, deprived sector loan, real estate loan and staff loan. The study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2015/16 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, reports published by Ministry of Finance and annual report of respective commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of credit diversification on the credit risk of Nepalese commercial banks. The study showed that overdraft loan has a negative effect on non-performing loan and net interest margin. It means that increase in overdraft loans leads to decrease in non performing loan and net interest margin. Similarly, term loan has a positive effect on non performing loan. It means that increase in term loans leads to increase in non-performing loan. In addition, deprived sector loan has a positive effect on non-performing loan. It means that increase in deprived sector loan leads to increase in non-performing loan. Likewise, real estate loan has a negative effect on non-performing loan and net interest margin. It means that increase in real estate loan leads to decrease in non-performing loan and net interest margin. Moreover, staff loan has a positive effect on non-performing loan and net interest margin. It means that increase in staff loan leads to increase in non-performing loan and net interest margin.